Implementation of Safety and Security Management Systems in Maritime Transportation (Professional Perspectives and Implementation Challenges) - Giovanni Battista Puteri; Abdul Rochman (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2025)
This qualitative study examines the implementation of safety and security management systems in maritime transportation through professional perspectives of 20 maritime industry stakeholders. The research analyzes implementation experiences with International Safety Management (ISM) Code and International Ship and Port Facility Security (ISPS) Code frameworks, identifying critical challenges, adaptive strategies, and competency development needs. Using thematic analysis of semi-structured interviews with maritime professionals, recent graduates, and educators, the study reveals significant gaps between theoretical frameworks and practical implementation realities. Findings indicate that professionals develop informal adaptation strategies to navigate conflicts between safety and security priorities, while educational preparation inadequately addresses real-world implementation complexities. The research contributes evidence-based implementation guidance for maritime organizations and recommendations for educational enhancement in maritime safety and security management competency development.